Incidence and clinical characteristics of transfusion‐associated circulatory overload using an active surveillance algorithm. Issue 1 (21st December 2016) - Roubinian, N. H.; Hendrickson, J. E.; Triulzi, D. J.; Gottschall, J. L.; Chowdhury, D.; Kor, D. J.; Looney, M. R.; Matthay, M. A.; Kleinman, S. H.; Brambilla, D.; Murphy, E. L.; ,
Abstract : Background: The concordance of haemovigilance criteria developed for surveillance of transfusion‐associated circulatory overload (TACO) with its clinical diagnosis has not been assessed. In a pilot study to evaluate an electronic screening algorithm, we sought to examine TACO incidence and application of haemovigilance criteria in patients with post‐transfusion pulmonary oedema. Study Design and Methods: From June to September 2014, all transfused adult inpatients at four academic hospitals were screened with an algorithm identifying chest radiographs ordered within 12 h of blood component release. Patients with post‐transfusion pulmonary oedema underwent case adjudication by an expert panel. TACO incidence was calculated, and clinical characteristics were compared with other causes of post‐transfusion pulmonary oedema. Results: Among 4932 transfused patients, there were 3412 algorithm alerts, 50 cases of TACO and 47 other causes of pulmonary oedema. TACO incidence was 1 case per 100 patients transfused. TACO classification based on two sets of haemovigilance criteria (National Healthcare Safety Network and proposed revised International Society for Blood Transfusion) was concordant with expert panel diagnosis in 57% and 54% of reviewed cases, respectively. Although the majority of clinical parameters did not differentiate expert panel adjudicated TACO from other cases, improved oxygenation within 24 h of transfusion did ( P = 0·01). Conclusions: The incidence of TACO was similar to that observed in prior studies utilizing active surveillance. Case classification by haemovigilance criteria was frequently discordant with clinical diagnoses of TACO in patients with post‐transfusion pulmonary oedema. Improvements in oxygenation within 24 h of transfusion merit further evaluation in the diagnosis of TACO.